1981
DOI: 10.1111/j.1440-1681.1981.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sustained Hypernatraemia on the Renin‐aldosterone System in the Dog

Abstract: 1. To determine if increases in plasma sodium concentration P[Na] have any sustained effects of the renin-aldosterone system, P[Na] was increased in a group of six dogs over a period of 6 days by increasing sodium intake from 10 to 200 mmol per day while a fixed 700 ml per day water intake was maintained along with a continuous i.v. infusion of antidiuretic hormone (ADH) at a rate of 2.4 units per day. 2. P[Na] rose from 137.3 +/- 2.0 to 153.6 +/- 6.5 mmol/l during the high intake period. Plasma potassium conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In a study similar to the present study, the same increase in sodium concentration for 6 days had no effect on arterial pressure or plasma renin activity. 27 In an acute study, Cowley and Lohmeier 28 demonstrated that a similar degree of hypernatremia did not affect the pressor response to angiotensin II in the intact dog. Furthermore, three intensively studied experimental models that typically have elevated plasma sodium concentrations (the Brattleboro rat; the lateral, ventral, third ventricle-lesioned rat; and the deoxycorticosterone-salt hypertensive rat) do not have any cardiovascular abnormalities attributed to their hypernatremia.…”
mentioning
confidence: 97%
“…In a study similar to the present study, the same increase in sodium concentration for 6 days had no effect on arterial pressure or plasma renin activity. 27 In an acute study, Cowley and Lohmeier 28 demonstrated that a similar degree of hypernatremia did not affect the pressor response to angiotensin II in the intact dog. Furthermore, three intensively studied experimental models that typically have elevated plasma sodium concentrations (the Brattleboro rat; the lateral, ventral, third ventricle-lesioned rat; and the deoxycorticosterone-salt hypertensive rat) do not have any cardiovascular abnormalities attributed to their hypernatremia.…”
mentioning
confidence: 97%